Pandangan dunia humanisme dalam film “air mata di ujung sajadah” yang disutradarai oleh key mangunsong berdasarkan perspektif lucien goldmann - Anggraini, Novia Retnowati (Maliki Interdisciplinary Journal, 2025)
Literary works are social events that occur in people’s lives which are then expressed in various forms. The author’s worldview is closely related to the conditions of a community group so that it can be a representative of a social class to express an opinion on an event that occurs. The form of worldview can be seen from the narration or dialog between characters. This research aims to reveal the forms of humanism worldview in the movie "Air Mata di Ujung Sajadah" directed by Key Mangunsong based on Lucien Goldmann’s perspective. The research method used is descriptive qualitative with primary data sources in the form of dialog between characters in the film "Air Mata di Ujung Sajadah". While secondary data sources in this study use data relevant to the object of research study, such as articles or journals. The method used in data collection is the watch, listen and record method to find data that is in accordance with the research. Then the data is analyzed using the Miles and Huberman method which consists of data collection, data reduction, data presentation and then drawing conclusions. The results of this study found forms of humanism worldview with details of 2 data showing compassion, 2 data showing concern for others, and 2 data showing sacrifice. The conclusion of this research is that the relationship between characters, ideas and ideas expressed in the movie is the director’s worldview or response to an event that occurs in the community. This is because the director or author of the movie story is a social member of a particular group. The director’s position here is a representative of a certain social class group to convey his aspirations or opinions through the films created.